A Systematic Literature Review: Behavioral Counseling Interventions in Overcome Childhood Sexual Abuse - Kawai Hilwa Safa Kirana; Pipit Novrianti; Edwindha Prafitra Nugraheni (Universitas Negeri Semarang, 2024)
Child sexual abuse tends to occur in close relationships, such as family and friendships. Abuse that has occurred in children can affect behavioral and emotional trauma in adulthood. According to the Kementerian Pemberdayaan Perempuan dan Perlindungan Anak (2024) from January 1st 2024 to the to the present the number of victims reached 12.558, with a percentage of underage victims 20.6% of victims with an age range of 6-12 years and 35.5% age range 13-17 years. This study aims to determine behavioral counseling interventions in overcoming cases of child sexual abuse. One of the behavioral counseling approaches that can be done to help children overcome trauma due to sexual abuse cases is by using Trauma-Focused Cognitive Behavioral Therapy (TF-CBT). This is done to reduce traumatic symptoms and increase self-confidence in children. This study uses the Systematic Literature Review (SLR) qualitative research method to identify and analyze articles relevant to the topic and to answer specific research questions. Articles found in the period 2020 to 2024 by searching google scholar articles through Harzing's Publish or Perish 8 (PoP) application reached 100 publications. Then only 5 articles were selected after making restrictions. Based on the literature collected, it shows that behavioral counseling with the TF-CBT approach is effective in overcoming post-traumatic symptoms in victims of sexual harassment. For future researchers, it is hoped that they can identify TF-CBT in victims who have different backgrounds. Pelecehan seksual terhadap anak cenderung terjadi dalam hubungan dekat, seperti keluarga dan persahabatan. Kekerasan yang terjadi pada anak dapat berdampak pada trauma perilaku dan emosional di masa dewasa. Menurut Kementerian Pemberdayaan Perempuan dan Perlindungan Anak (2024) sejak 1 Januari 2024 hingga saat ini jumlah korban mencapai 12.558 orang, dengan persentase korban di bawah umur 20,6%, korban dengan rentang usia 6-12 tahun dan 35,5% rentang usia 13-17 tahun. Penelitian ini bertujuan untuk mengetahui intervensi konseling behavioral dalam mengatasi kasus pelecehan seksual pada anak. Salah satu pendekatan konseling perilaku yang dapat dilakukan untuk membantu anak mengatasi trauma akibat kasus pelecehan seksual adalah dengan menggunakan Trauma-Focused Cognitive Behavioral Therapy (TF-CBT). Hal ini dilakukan untuk mengurangi gejala traumatis dan meningkatkan rasa percaya diri pada anak. Penelitian ini menggunakan metode penelitian kualitatif Systematic Literature Review (SLR) untuk mengidentifikasi dan menganalisis artikel yang relevan dengan topik dan untuk menjawab pertanyaan penelitian yang spesifik. Artikel yang ditemukan pada periode 2020 hingga 2024 dengan pencarian artikel google Scholar melalui aplikasi Harzing's Publish or Perish 8 (PoP) mencapai 100 publikasi. Kemudian yang terpilih hanya 5 artikel setelah dilakukan pembatasan. Berdasarkan literatur yang dikumpulkan menunjukkan bahwa konseling behavioral dengan pendekatan TF-CBT efektif mengatasi gejala pasca trauma pada korban pelecehan seksual. Bagi peneliti selanjutnya diharapkan dapat mengidentifikasi TF-CBT pada korban yang memiliki latar belakang berbeda.